Автомат складання вузла контакту магнітної пробки - Коруняк, П. С.; Боровець, В. М. (Видавництво Національного університету «Львівська політехніка», 2001)
The operation of assembly of an item is final in a manufacturing process of his manufacturing. As this operation concerns to monotonic and wearisome operation that creation of means of automation for its fulfilment - with a major problem of engineering. The offered construction of an assembly automaton of contact of a magnetic fuse of an automobile gas system is considered. The construction of an automaton as a whole and his actuators in particular, and also their principle of operation is circumscribed.